L-type Ca2+ channels, Ca2+-induced Ca2+ release, and BKCa channels in airway stretch-induced contraction - Hernandez, Jeremy Mark; Janssen, Luke Jeffrey (European journal of pharmacology, 2012)
Resistance arteries constrict in response to mechanical stress. This response is myogenic in nature, and reliant on membrane depolarization, activation of L-type Ca2+ channels, Ca2+-induced Ca2+-release and large conductance Ca2+-dependent K+ channels (BKCa). Airway smooth muscle is also affected by mechanical stress: a deep inspiration produces a bronchodilation in healthy individuals, but bronchoconstriction in moderate to severe asthmatics. In this study, our objective was to investigate the regulation of this airway stretch-activated contractile response (Rstretch), and explore its similarities to the vascular myogenic response. Using a pharmacological approach in intact bovine bronchial segments cannulated horizontally in an organ bath, we showed the ability of carbachol (2-carbamoyloxyethyl-trimethyl-azanium), KCl, neurokinin-A, and U46619 (9,11-dideoxy-9α,11α-methanoepoxy-prosta-5Z, 13E-dien-1-oic acid) to generate Rstretch in a concentration-dependent manner. Rstretch was significantly reduced by nifedipine, ryanodine, and iberiotoxin, suggesting that it possesses characteristics similar to those of the vascular smooth muscle myogenic response, such as a role for membrane depolarization, L-type Ca2+ channel, ryanodine receptors and BKCa channel activation. This study demonstrates a novel role for the L-type Ca2+ channel in airway smooth muscle and provides new insights into possible mechanisms regulating the deep inspiration-induced bronchoconstriction seen in asthmatics.